Genomic and physiological properties of Anoxybacterium hadale gen. nov. sp. nov. reveal the important role of dissolved organic sulfur in microbial metabolism in hadal ecosystems - Cao, Junwei; Shao, Baoying; Lin, Jing; Liu, Jie; Cui, Yiran; Wang, Jiahua; Fang, Jiasong (Frontiers in Microbiology, 2024)
Hadal zones account for the deepest 45 % of the oceanic depth range and play an important role in ocean biogeochemical cycles. As the least-explored aquatic habitat on earth, hadal ecosystems contain a vast diversity of so far uncultured microorganisms that cannot be grown on conventional laboratory culture media. Therefore, it has been difficult to gain a true understanding of the detailed metabolic characteristics and ecological functions of those difficult-to-culture microorganisms in hadal environments. In this study, a novel anaerobic bacterial strain, MT110T, was isolated from a hadal sediment-water interface sample of the Mariana Trench at 10890 m. The level of 16S rRNA gene sequence similarity and percentage of conserved proteins between strain MT110T and the closest relatives, Anaerovorax odorimutans DSM 5092T (94.9 % and 46.6 %) and Aminipila butyrica DSM 103574T (94.4 % and 46.7 %), indicated that strain MT110T exhibits sufficient molecular differences for genus-level delineation. Phylogenetic analyses based on both 16S rRNA gene and genome sequences showed that strain MT110T formed an independent monophyletic branch within the family Anaerovoracaceae. The combined evidence showed that strain MT110T represents a novel species of a novel genus, proposed as Anoxybacterium hadale gen. nov. sp. nov. (type strain MT110T = KCTC 15922T= MCCC 1K04061T), which represents a previously uncultured lineage of the class Clostridia. Physiologically, no tested organic matter could be used as sole carbon source by strain MT110T. Genomic analysis showed that MT110T had the potential capacity of utilizing various carbon sources, but the pathways of sulfur reduction were largely incomplete. Our experiments further revealed that cysteine is one of the essential nutrients for the survival of strain MT110T, and cannot be replaced by sulfite, leucine, or taurine. This result suggests that organic sulfur compounds might play an important role in metabolism and growth of the family Anaerovoracaceae and could be one of the key factors affecting the cultivation of the uncultured microbes. Our study brings a new perspective to the role of dissolved organic sulfur in hadal ecosystems and also provides valuable information for optimizing the conditions of isolating related microbial taxa from the hadal environment.